1983
DOI: 10.1111/j.1365-2273.1983.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and otosclerosis

Abstract: A retrospective study has been made of a sample of 479 women with deafness from otosclerosis, classified according to the number of pregnancies they have had and whether there had been a subjective impression of deterioration of hearing during or immediately after at least 1 pregnancy. The study confirms previous reports that pregnancy does involve a risk of aggravating deafness in clinical otosclerosis. The chance of female patients with bilateral otosclerosis reporting a subjective deterioration of hearing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…For instance, Gristwood and Venables [5] found that 33% of female patients with otosclerosis reported deterioration of hearing after one pregnancy and 63% after six pregnancies. One might therefore assume that in women the hearing impairment caused by otosclerosis will advance more rapidly than in men.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gristwood and Venables [5] found that 33% of female patients with otosclerosis reported deterioration of hearing after one pregnancy and 63% after six pregnancies. One might therefore assume that in women the hearing impairment caused by otosclerosis will advance more rapidly than in men.…”
Section: Discussionmentioning
confidence: 99%
“…While otosclerosis is reported to worsen during periods of intense hormonal activity (Sellari-Franceschini et al, 1998), a possible link between aggravation of otosclerosis and pregnancy is still debated. A retrospective study on a sample of 479 women with otosclerosis showed that the risk of subjective hearing deterioration with bilateral otosclerosis increased from 33% after one pregnancy to 63% after six pregnancies (Gristwood and Venables, 1983). On the other hand, a retrospective study on women, who had undergone stapedectomy, found no significant correlation between number of children and hearing loss (Lippy et al, 2005).…”
Section: Hormones and Otosclerosismentioning
confidence: 97%
“…Hearing loss related to cochlear otosclerosis worsens during periods of intense hormonal activity (83). Otosclerosis often begins during a first pregnancy and is seriously aggravated during successive pregnancies (38).…”
Section: Discussionmentioning
confidence: 99%